The anticancer potential of the dietary polyphenol rutin: Current status, challenges, and perspectives - Farha, Arakkaveettil Kabeer; Gan, Ren-You; Li, Hua-Bin; Wu, Ding-Tao; Atanasov, Atanas G.; Gul, Khalid; Zhang, Jia-Rong; Yang, Qiong-Qiong; Corke, Harold (Critical reviews in food science and nutrition, 2022)
Rutin is one of the most common dietary polyphenols found in vegetables, fruits, and other plants. It is metabolized by the mammalian gut microbiota and absorbed from the intestines, and becomes bioavailable in the form of conjugated metabolites. Rutin exhibits a plethora of bioactive properties, making it an extremely promising phytochemical. Numerous studies demonstrate that rutin can act as a chemotherapeutic and chemopreventive agent, and its anticancer effects can be mediated through the suppression of cell proliferation, the induction of apoptosis or autophagy, and the hindering of angiogenesis and metastasis. Rutin has been found to modulate multiple molecular targets involved in carcinogenesis, such as cell cycle mediators, cellular kinases, inflammatory cytokines, transcription factors, drug transporters, and reactive oxygen species. This review summarizes the natural sources of rutin, its bioavailability, and in particular its potential use as an anticancer agent, with highlighting its anticancer mechanisms as well as molecular targets. Additionally, this review updates the anticancer potential of its analogs, nanoformulations, and metabolites, and discusses relevant safety issues. Overall, rutin is a promising natural dietary compound with promising anticancer potential and can be widely used in functional foods, dietary supplements, and pharmaceuticals for the prevention and management of cancer.